Penerapan Metode Analytical Hierarchy Process (Ahp) Pada Sistem pendukung keputusan Penentuan Taman Kanak-Kanak - Delsiana Bili delsi; Gergorius Kopong Pati; Dian Fransiska Ledi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
The problem of parents who have young children at the beginning of each new school year is choosing a kindergarten school. Choosing a school in early childhood is not a young thing because there are many difficulties caused by criteria that parents must know. The Decision Support System (SPK) is a solution in providing considerations to parents in choosing a kindergarten school. Analytical Hierarchy Process (AHP) is a method that has a hierarchical structure and makes it easy to simplify a problem from complex criteria with various alternative options available, so that it can speed up the decision-making process in selecting a Kindergarten. The criteria used in selecting the best Kindergarten consist of 6 (six) criteria, namely accreditation, infrastructure, tuition fees, curriculum, number of teachers and number of students. The final result of data processing and testing using the Analytical Hierarchy Process (AHP) method can be determined that the best Kindergarten is Waikalasung with the highest final score calculation result of 1 or 3.83%.